'Becoming an intellectual': how Congolese refugee university-students in Rwanda negotiate ideals, expectations and social positionality. (26th May 2020) - Fert, Marion
ABSTRACT: While the number of refugees in tertiary education remains small in comparison to the total number of refugee youths, with 1% of university-students worldwide, their social, economic and political impact in refugee societies is believed to be significant. Yet, the role of higher education in their socialisation, the way humanitarian actors invest in the field of higher education with specific agendas in mind and the ways that these young scholars position themselves in relation to these policies and discourses have remained largely unexplored. Focusing on Congolese refugees studying at a Rwandan University and supported by the world's largest academic scholarship programme funded and administrated by a UN agency, this paper aims to contribute to a better understanding of how students negotiate their identities as 'highly educated persons'. The analysis draws on various forms of what the humanitarian rhetoric calls 'community-based investment' with which students engage in the public space of the camps during summer or semester breaks. The different types of engagement that are discussed in this paper serve as a case study to examine how different understandings and perceptions of 'becoming an intellectual' coexist in individuals' minds, according to the different political subjectivities and regimes they navigate in.